The Effect of Mudharabah and Musyarakah Financing Risks on The Profitability of Sharia Commercial Banks in Indonesia - Rahmad Syahputra (TRIGIN PUBLISHER, 2021)
This study at to analyze the effect of mudharabah and musharakah to profitability. This research collects empirical evidence. The population in this study is the whole of financing, musharakah financing and return on assets of Islamic banks in Indonesia. The data is taken from the financial statements of income and statements of financial position. Based on this research, known variables influence mudharabah and musharakah has a significant effect on profitability simultaneously. Partially, the mudarabah variable has a positive effect, but no significant effect on profitability. While the musyarakah variable has a partially positive and significant impact on profitability.